(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Lentils could escape the infection of Stemphylium blight by changing sowing dates. During the periods of studies the trends of disease development were similar. The lowest and the highest severity were noted on November 01 and December 30, respectively. The severity increased progressively with the advancement of sowing date from November 01 to December 30. In case of yield/ha November 01 gave the highest yield followed by November 10. In the sowing of November 01, 10 and 20, lentil could escape the infection of Stemphylium blight. The yield was maximum in the early sown seeds of lentil. Key words: Stemphylium blight, Sowing dates, Disease incidence, Lentil and Yield Bangladesh J. Sci. Ind. Res. 42(3), 341-346, 2007